DESIGN AND DEVELOPMENT OF TARGET DESIGN WITH BASIC IMAGE PROCESSING ON OTHTT SYSTEM PROTOTYPE (OVER THE HORIZON TARGET TRACKING) - Sigit Purwanto; I Made Jiwa Astika; Erpan Sahiri; Ekaris K. Novarendra (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Based on Law No. 34 of 2004, the Indonesian Navy has the main task of maintaining state sovereignty in territorial waters. Various attempts have been made to strengthen the Navy so that it can carry out these basic tasks, one of which is to add defense equipment, namely ships that have the ability to shoot missiles. This missile possession is important because in addition to being a deterence effect, modern naval battles are dominated by long-distance warfare or Over The Horizon. In missile fire, accurate intelligence is needed to determine the position of the target. So far what has been done is sending submarines or reconnaissance aircraft. This is very inefficient because in addition to requiring large resources, the risk of losing personnel and material is also very large. Based on this, the researcher makes a prototype of a vehicle that can identify and determine the position of a target. The vehicle in the form of a UAV is equipped with GPS, altimeter, compass and camera. This equipment will provide data in the form of UAV latitude and longitude position, UAV height, UAV heading and UAV camera angle. From the four data above, the ground station on themissile carrier gets the target's latitude and longitude data based on image processing. While the method used is color thresholding which can distinguish a target based on its color. After several trials, the UAV has been able to carry out the target positioning up to a height of 15.4 meters. At these heights the target latitude can be determined with a system accuracy of 3.3 meters. To be used as a reference for missile firing, it is necessary to increase the capability of the equipment specifications to reach the desired distance. Keywords: Target, Latitude, Longitude, Image Processing.